2015
DOI: 10.1080/00140139.2015.1080861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the postural and physiological effects of two dynamic workstations to conventional sitting and standing workstations

Abstract: Increasing evidence is being found for the association of health risk factors with work-related physical inactivity. An increasing number of people are being exposed to this form of inactivity, and as a result, various interventions aimed at increasing physical activity during working hours are being developed. This study aims to investigate the differences in postural, muscular and physical activities resulting from two dynamic workstations, namely an elliptical trainer and a treadmill workstation, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
1
31
0
1
Order By: Relevance
“…Specifically, Botter et al 13 reported an increase of 12 beats per minute (bpm) using a treadmill 2.5 km/hour (91 bpm) compared with standing (79 bpm), which was corroborated by Cox et al 14. Moreover, Straker et al 15 reported an increase of 5 bmp for the treadmill 3.2 km/hour and an increase of 7 bmp for cycling 30 W  compared with standing workstations.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Specifically, Botter et al 13 reported an increase of 12 beats per minute (bpm) using a treadmill 2.5 km/hour (91 bpm) compared with standing (79 bpm), which was corroborated by Cox et al 14. Moreover, Straker et al 15 reported an increase of 5 bmp for the treadmill 3.2 km/hour and an increase of 7 bmp for cycling 30 W  compared with standing workstations.…”
Section: Resultsmentioning
confidence: 85%
“…One study13 examined the biomechanics of three active workstations using electromyography of the trapezius and erector spinae, trunk and head 3D kinematics and physical activity quantified by accelerometers on the legs, trunk and arms. Twelve participants were asked to complete general office tasks (ie, typing, reading, correction, telephone use, mouse dexterity and cognitive tasks) while using active workstations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations